2014
DOI: 10.1371/journal.pone.0090102
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic and Concerted Evolution in the Visual System of Birds

Abstract: Two main models have been proposed to explain how the relative size of neural structures varies through evolution. In the mosaic evolution model, individual brain structures vary in size independently of each other, whereas in the concerted evolution model developmental constraints result in different parts of the brain varying in size in a coordinated manner. Several studies have shown variation of the relative size of individual nuclei in the vertebrate brain, but it is currently not known if nuclei belongin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 121 publications
(173 reference statements)
2
42
0
Order By: Relevance
“…As the rhombencephalon contains nuclei important for processing sensory modalities other than vision, change in rhombencephalic and tectal volumes could represent evolutionary trade-offs between sensory modalities [Wylie et al, 2015]. Alternatively, visual nuclei can evolve as a mosaic [Gutiérrez-Ibáñez et al, 2014], and therefore the contrasting variations that we found in the rhombencephalon and tectum may represent various changes within the visual processing system. As sensory processing nuclei are generally small compared to the volumes of the subdivisions in which they are located, variations in the volume of individual nuclei are unlikely to result in detectable volumetric changes in the entire subdivision unless several nuclei change volume in concert.…”
Section: Concerted and Mosaic Brain Evolution In Lizardsmentioning
confidence: 77%
See 1 more Smart Citation
“…As the rhombencephalon contains nuclei important for processing sensory modalities other than vision, change in rhombencephalic and tectal volumes could represent evolutionary trade-offs between sensory modalities [Wylie et al, 2015]. Alternatively, visual nuclei can evolve as a mosaic [Gutiérrez-Ibáñez et al, 2014], and therefore the contrasting variations that we found in the rhombencephalon and tectum may represent various changes within the visual processing system. As sensory processing nuclei are generally small compared to the volumes of the subdivisions in which they are located, variations in the volume of individual nuclei are unlikely to result in detectable volumetric changes in the entire subdivision unless several nuclei change volume in concert.…”
Section: Concerted and Mosaic Brain Evolution In Lizardsmentioning
confidence: 77%
“…This dichotomy also exists between the major clades of fishes, with cartilaginous fishes primarily showing a concerted pattern of brain evolution [Yopak et al, 2010] whereas bony fishes seem to primarily exhibit a mosaic pattern [Kotrschal et al, 1998;Gonzalez-Voyer et al, 2009]. Though both evolutionary patterns occur together, it is generally thought that certain structures within the brain are driven by mosaic brain evolution, while others are driven by concerted evolution [Platel, 1976;Gutiérrez-Ibáñez et al, 2014]. A key question remains as to whether, and how, both patterns can interact to drive the evolution of a single brain structure.…”
Section: Introductionmentioning
confidence: 99%
“…A well-known example of this relationship is the association across birds between the relative volumes of brain regions involved in song production and the complexity of the species' song (e.g., DeVoogd et al, 1993;Brenowitz, 1997). Further, selection can act on the relative sizes of different regions of the brain independently of overall brain size (i.e., mosaic evolution) in taxa as diverse as mammals, birds, and fish (e.g., Barton and Harvey, 2000;Iwaniuk et al, 2004;Pollen et al, 2007;Smaers and Soligo, 2013;Gutiérrez-Ibáñez et al, 2014). The influence of natural selection on brain morphology is particularly relevant in the evolution of the sensory systems that allow an animal to interact with its environment.…”
Section: Discussionmentioning
confidence: 99%
“…Gutiérrez-Ibáñez et al 2014, Lefebvre 2014, Reyes and Sherwood 2014. In fact, two misconceptions were commonly associated with this dual view of brain evolution.…”
Section: A3 More On Brain and Allometrymentioning
confidence: 99%